Prompt gamma spectroscopy for range control with CeBr3 - Martins Paulo Magalhaes; Dal Bello Riccardo; Rinscheid Andreas; Roemer Katja; Werner Theresa; Enghardt Wolfgang; Pausch Guntram; Seco Joao (Current Directions in Biomedical Engineering, 2017)
The ultimate goal of radiotherapy using external beams is to maximize the dose delivered to the tumor while minimizing the radiation given to surrounding healthy critical organs. Prompt Gamma Spectroscopy (PGS) has been proposed for range control of particle beams along with the determination of the elemental composition of irradiated tissues. We aim at developing a PGS system for the German Cancer Research Center – DKFZ that takes advantage of the superior selectivity of Helium and Carbon beams accelerated at the Heidelberg Ion-Beam Therapy Center. Preliminary tests with protons accelerated with an IBA C230 cyclotron located at the Universitäts Protonen Therapie Dresden were performed at OncoRay – National Center for Radiation Re-search in Oncology. We present results obtained with a PGS system composed of CeBr3 detectors (Ø 2’’ × 2’’) and (Ø 1.5’’ × 3’’) coupled to a Hamamatsu R13089 photomulti-plier tube and plugged to a Target U100 Spectrometer. Such system provides accurate time-of-flight measurements to increase the signal-to-noise ratio relative to neutron-induced background. First measurements resulted from the irradiation of PMMA and water phantoms, and graphite and aluminum bricks. Several PG energy lines ranging from 0.511 MeV up to 8 MeV were identified and compared with reference re-sults. Two further experiments consisted in irradiating PMMA phantoms in a slit- and semi-collimated configuration with mono-energetic proton beams of 165 MeV and 224 MeV, respectively. Results acquired by means of trans-versal PGS at different phantom depths, ranging from 6 cm before the Bragg peak (BP) to 3.5 cm beyond the BP in 5 mm steps with a 1 cm slit collimation (tungsten) showed a slight decrease of PG yields after the BP. Similar measurements with a semi-opened collimation configuration demonstrated a steeper decrease of PG yields after the BP.